Do Hedge Fund Managers Misreport Returns? Evidence from the Pooled Distribution - BOLLEN, NICOLAS P.B.; POOL, VERONIKA K. (Journal of Finance, 2009)
ABSTRACT We find a significant discontinuity in the pooled distribution of monthly hedge fund returns: The number of small gains far exceeds the number of small losses. The discontinuity is present in live and defunct funds, and funds of all ages, suggesting that it is not caused by database biases. The discontinuity is absent in the 3 months culminating in an audit, suggesting it is not attributable to skillful loss avoidance. The discontinuity disappears when using bimonthly returns, indicating a reversal in fund performance following small gains. This result suggests that the discontinuity is caused at least in part by temporarily overstated returns.